Temperature-driven structural phase transition in double perovskite Bi2FeCrO6 films. (18th December 2019) - Meng, Dehuan; Kang, Tongtong; Bi, Lei; Zhang, Huaiwu; Zhai, Junyi; Bai, Feiming
Abstract: Epitaxial Bi2 FeCrO6 films with strong 1/2 1/2 1/2 and 3/2 3/2 3/2 superlattice-diffraction peaks exhibit dramatically enhanced spontaneous polarization. In current work, temperature-dependent X-ray diffraction and Raman scattering have been performed. It is shown that the superlattice peaks disappear above 650 K, in accompany with a rhombohedral-to-tetragonal structural phase transition. Raman spectra evidence the disappearance of A1 (LO) modes and a first red shift but then blue shift of an Ag -like mode from 550 to 700 K. These observations suggest that the superlattice structure may come from A- or B-site cation shifts along the pseudo-cubic [111] direction, which contributes to the enhanced spontaneous polarization.